Disrupting cisheteronormativity in STEM through humanism - Jones, Meg C.; Forsythe, Desiree; Friedensen, Rachel; Vaccaro, Annemarie; Miller, Ryan A.; Kimball, Ezekiel; Forester, Rachael (Frontiers in Education, 2023)
Cisheteronormativity is prevalent throughout college STEM discourses and classrooms. In this paper, we present findings from a U.S. based study focused on the experiences of collegiate STEM students with minoritized identities of sexuality and gender (MIoSG) as the backdrop for discussing how current harmful ideologies in STEM perpetuate cisheteronormativity through discursive practice. We propose that humanistic classrooms and pedagogy can work to dismantle cisheteronormative D/discourses in STEM and create MIoSG inclusive STEM classrooms and programs. Our findings highlight the ways participants experienced cisheteronormative D/discourses in their collegiate STEM contexts. We discuss how these experiences might be mitigated through humanistic educational approaches in college STEM contexts. Our aim is for readers to gain simultaneous theoretical and pragmatic insights on how cisheteronormative D/discourses operate in collegiate STEM classrooms and educational programs.